Evaluation of the effects of a cultural-based support group for Malay dementia caregivers in Kelantan, Malaysia - Zakaria, Rozanizam (2017)
Introduction: The psychological impact of caregiving responsibility for dementia patients is significant regardless of the cultural background. Most of the current advanced caregivers’ interventions, originating from developed western countries, do not necessarily apply to local settings. Hence, there is a need for an effective culturally competent psychological intervention for these caregivers. Objectives: To compare the level of burden, stress, anxiety, and quality of life among caregivers pre and post-intervention. Methods: This was an experimental study, without control, investigating pre and post support group intervention effectiveness in reducing caregiver burden, anxiety and depression, and improving the quality of life. Sixteen caregivers completed the program, which involved seven fortnightly support group sessions with duration of 2 hours each, conducted over twelve weeks from June 2015 until January 2017. Caregivers’ burden was assessed using Caregiver Strain Index (CSI) while their psychological well-being was objectively assessed using Hospital Anxiety and Depression Scale (HADS). WHO Quality of Life questionnaire (WHOQOL-BREF) was used to measure the quality of life. The validated Malay versions of the questionnaires were used.Results: There was a statistically significant reduction in the level of caregiver burden (p: 0.03). Measurement of both scores of anxiety and depression comparing pre and postintervention also showed improvement, but statistically were not significant. Assessment of caregivers’ quality of life showed statistically significant improvement in the domains of social, psychological and physical (all with p-value <0.05). Discussion: Our cultural-based support group had effects in improving burden, psychological well-being and quality of life among local caregivers of dementia patients.